2019
DOI: 10.1007/s00122-019-03327-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of training population design on genomic prediction accuracy in wheat

Abstract: Genomic selection offers several routes for increasing the genetic gain or efficiency of plant breeding programmes. In various species of livestock, there is empirical evidence of increased rates of genetic gain from the use of genomic selection to target different aspects of the breeder’s equation. Accurate predictions of genomic breeding value are central to this, and the design of training sets is in turn central to achieving sufficient levels of accuracy. In summary, small numbers of close relatives and ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 34 publications
12
65
0
Order By: Relevance
“…Except for the three traits in TP17 and DIS in TP18, the small sized population selected by stratified sampling also had higher predictive abilities than when the entire TP was used. Similar to our findings, several studies [23][24][25]43] have shown that a small TP with closely related lines had a greater predictive ability than a same-sized or larger TP with less-related lines.…”
Section: Small Population Sizesupporting
confidence: 92%
See 1 more Smart Citation
“…Except for the three traits in TP17 and DIS in TP18, the small sized population selected by stratified sampling also had higher predictive abilities than when the entire TP was used. Similar to our findings, several studies [23][24][25]43] have shown that a small TP with closely related lines had a greater predictive ability than a same-sized or larger TP with less-related lines.…”
Section: Small Population Sizesupporting
confidence: 92%
“…After 2017, our goal was to design an optimized training population (TP) that minimized the cost of phenotyping for FHB resistance while maximizing prediction accuracy for the untested lines. While simulation and empirical results have shown improved prediction accuracies when TP size is increased [17][18][19][20][21], other studies have achieved high accuracies with smaller TP sizes that were more closely related to the breeding population and lower accuracies as TP became more unrelated to the breeding population [22][23][24][25]. For example, Rincent et al [22] found that an optimized set of 100 lines achieved the same prediction accuracy as a set of 200 lines selected at random.…”
Section: Introductionmentioning
confidence: 99%
“…These results were further supported by the highly significant (p>2.2e -16 ) positive correlation (R=0.92) between TS size and PAs. Similarly, positive correlations between the number of lines in the TS and the PAs, and plateau for the PAs were also reported by Edwards et al (111).…”
Section: Influence Of the Size And The Composition Of Ts And Bs On Passupporting
confidence: 81%
“…A net increase in PAs for maize resistance to FAW was realized when the size of the TS was increased from 37% (0.694 to 0.714) to 63% (0.833 to 0.838) similar to earlier reports on wheat yield (111). This increase was followed by a slight gain in predictability at 75% (0.837 to 0.843) and 85% (0.843 to 0.847), and thus, the PAs plateaued when TS sizes above 63% were considered in this study as reported earlier in other studies (21,64,(111)(112)(113). Thus, future GS programs for maize resistance to FAW could be designed around TS composed of a minimum of 60% of the entire breeding germplasm to achieve high genetic gains.…”
Section: Influence Of the Size And The Composition Of Ts And Bs On Passupporting
confidence: 67%
“…A positive correlation between prediction accuracy and TRN size was confirmed in several species [ 76 , 77 ]. However, the optimal TRN size seems to be highly influenced by the relatedness of TRS and TST [ 25 , 78 , 79 ]. The highest prediction accuracies were found using TRS with a strong relationship to the TST [ 28 , 80 , 81 ].…”
Section: Tomato Gs Schema Implementationmentioning
confidence: 99%